PENGGUNAAN METODE TUTOR SEBAYA SEBAGAI UPAYA MENINGKATKAN PARTISIPASI DAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI MATERI PERMINTAAN DAN PENAWARAN KELAS X-2 DI SMA NEGERI 1 ANGSANA SEMESTER GANJIL TAHUN PELAJARAN 2013/2014 - Amrullah Amrullah (JURNAL SOCIUS, 2017)
The Peer Tutor Methods is used to Increase Participation and Learning Outcomes of Students in Economics Subject Matter Demand and Supply Class X-2 at SMA Negeri 1 Angsana Odd Semester Academic Year 2013/2014. The aims of research to increase the participation and student learning outcomes in learning on the subjects of Economics. This study used action research method. Therefore, there were quantitative and qualitative approaches. The results showed that the activity of teachers' activities showed an increase of 4.17%. Learning activities of teachers in the first cycle of 93.75% and 97.92% for the second cycle. Learning student participation in study showed an increase of 10.5%. Participation of students in the first cycle of 72.54% and the second cycle of 83.04%. Individualized student learning outcomes showed a 11.84% increase. The average value of individual learning outcomes of students in the first cycle of 67.97 and 79.81 for the second cycle. Classical learning completeness showed an increase of 25%. The percentage of mastery learning in the first cycle of 65.63% and 90.63% for the second cycle. Keywords: Peer tutoring method, Participation and Learning Outcomes